2013
DOI: 10.1177/194008291300600606
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Occupancy Modeling and Camera-Trap Data to Estimate Medium and Large Mammal Detection and Richness in a Central American Biological Corridor

Abstract: Noninvasive camera-traps are commonly used to survey mammal communities in the Neotropics. This study used camera-traps to survey medium and large mammal diversity in the San Juan-La Selva Biological Corridor, Costa Rica. The connectivity of the corridor is affected by the spread of large-scale agriculture, cattle ranching, and a growing human presence. An occupancy modeling approach was used to estimate corridor species richness and species-specific detection probabilities in 16 forested sites within four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
5
31
0
4
Order By: Relevance
“…Given the high conservation value of T. pinchaque, it is imperative to validate to what extent the SFFOQ provides this species protection or shelter, considering the pressures it endures. Conclusions by Cove et al (2013) support this idea.…”
Section: Universitas Scientiarum Vol 22 (1): 9-29supporting
confidence: 73%
See 3 more Smart Citations
“…Given the high conservation value of T. pinchaque, it is imperative to validate to what extent the SFFOQ provides this species protection or shelter, considering the pressures it endures. Conclusions by Cove et al (2013) support this idea.…”
Section: Universitas Scientiarum Vol 22 (1): 9-29supporting
confidence: 73%
“…In Mexico, Lira- Torres & Briones-Salas (2012) found that in an area where subsistence hunting was practiced, T. bairdii presented nocturnal and crepuscular habits. It was suggested in a study by Cove et al (2013) and supported in this study by the abundance of photographic records that an increase in human presence may compel a high number of infrequent species to move to and concentrate in areas that provide them with suitable habitat. This suggests that T. pinchaque might be concentrated in dense cover areas (SF) within the SFFOQ possibly to avoid human presence.…”
Section: Universitas Scientiarum Vol 22 (1): 9-29mentioning
confidence: 96%
See 2 more Smart Citations
“…This approach has the differential of dealing with imperfect detection, because individuals may not be detected due to sampling limitations or low population density, which is common issue for several species of medium and large-sized tropical mammals (Mackenzie et al 2002, O'Connell et al 2006. Furthermore, occupancy models are a powerful tool to analyze the influence of landscape covariates and habitat changes on species occurrence (Nicholson & Manen 2009, Cove 2011). …”
Section: Introductionmentioning
confidence: 99%